Post-pandemic era user experience model and technology acceptance for online teaching platforms in China - Mei, Wang; Ramasamy, Siva Shankar; Dawod, Ahmad Yahya (International Journal of Innovative Research and Scientific Studies, 2025)
In the context of the global COVID-19 pandemic and its aftermath, online teaching has become an indispensable component of the education sector. However, with the widespread adoption of online teaching, schools, teachers, students, and parents face numerous challenges in accessing, utilizing, and evaluating online teaching platforms. One of the most pressing issues is the inadequacy of user experience and the lack of a tailored user experience model. This study, taking the Chao Xing Online Teaching Platform as an example, delves into the construction and optimization of user experience for online teaching platforms. By integrating the content structure of user experience, relevant theoretical models, and the functional characteristics of online teaching platforms, this research formulates a User Experience Model specifically for the Chao Xing Online Teaching Platform. This model incorporates key factors from teacher evaluation models and integrates the theoretical framework of the Technology Acceptance Model, aiming to provide users with clearer and more systematic navigation and an enhanced online teaching experience. The goal of this study is to provide guidance for developers of the Chao Xing Online Teaching Platform in terms of design and development, prioritize user experience, and elevate construction standards, ultimately creating a superior and satisfying online teaching environment that lays a solid foundation for the future development of intelligent teaching.